THE RELEVANCE OF THE VALUE OF ASSETS IN MANUFACTURING COMPANIES LISTED IN BEI FOR THE PERIOD OF 2011--2020 - Rika Cheriani; Carmel Meiden (Jurnal Akuntansi, 2022)
Book value and profit are considered relevant financial information. However, in some cases, the value relevance of profit and book value has decreased. This causes investors to look for other financial information, such as intangible assets. Intangible assets can be used as an indicator in measuring the relevance and a relevant proxy for expected future earnings because they are considered the driver of company growth and productivity nowadays. This study used the multiple linear regression method. The object of this study is manufacturing companies listed on the Indonesia Stock Exchange. The samples are selected using the purposive sampling method. The findings of this study are that profit, book value, and intangible assets have a significant and positive effect. This study hopes that investors can use intangible assets as additional information to predict investment returns and make investment decisions.